A school-based physical activity promotion intervention in children: rationale and study protocol for the PREVIENE Project - Pablo Tercedor; Emilio Villa-González; Manuel Ávila-García; Carolina Díaz-Piedra; Alejandro Martínez-Baena; Alberto Soriano-Maldonado; Isaac José Pérez-López; Inmaculada García-Rodríguez; Sandra Mandic; Juan Palomares-Cuadros; Víctor Segura-Jiménez; Francisco Javier Huertas-Delgado (BMC, 2017)
Abstract Background The lack of physical activity and increasing time spent in sedentary behaviours during childhood place importance on developing low cost, easy-toimplement school-based interventions to increase physical activity among children. The PREVIENE Project will evaluate the effectiveness of five innovative, simple, and feasible interventions (active commuting to/from school, active Physical Education lessons, active school recess, sleep health promotion, and an integrated program incorporating all 4 interventions) to improve physical activity, fitness, anthropometry, sleep health, academic achievement, and health-related quality of life in primary school children. Methods A total of 300 children (grade 3; 8-9 years of age) from six schools in Granada (Spain) will be enrolled in one of the 8-week interventions (one intervention per school; 50 children per school) or a control group (no intervention school; 50 children). Outcomes will include physical activity (measured by accelerometry), physical fitness (assessed using the ALPHA fitness battery), and anthropometry (height, weight and waist circumference). Furthermore, they will include sleep health (measured by accelerometers, a sleep diary, and sleep health questionnaires), academic achievement (grades from the official school's records), and health-related quality of life (child and parental questionnaires). To assess the effectiveness of the different interventions on objectively measured PA and the other outcomes, the generalized linear model will be used. Discussion The PREVIENE Project will provide the information about the effectiveness and implementation of different school-based interventions for physical activity promotion in primary school children.